Free-standing 2D non-van der Waals antiferromagnetic hexagonal FeSe semiconductor: halide-assisted chemical synthesis and Fe2+ related magnetic transitions. Issue 1 (9th December 2021) - Xu, Junjie; Li, Wei; Zhang, Biao; Zha, Liang; Hao, Wei; Hu, Shixin; Yang, Jinbo; Li, ShuZhou; Gao, Song; Hou, Yanglong
Abstract : Free-standing two-dimensional non-layered hexagonal FeSe with intrinsic antiferromagnetic and semiconducting nature has been achieved by a wet-chemical method. The chemical environment change of Fe 2+ would induce the magnetic transition of FeSe. Abstract : The scarcity of two-dimensional (2D) magnetic nanostructures has hindered their applications in spintronics, which is attributed to that most magnetic materials exhibit non-van der Waals (nvdWs) structures and it is hard to reduce their thickness to 2D nanostructures. Thus it is necessary to develop a promising strategy for free-standing 2D magnetic nvdWs nanostructures. We have achieved free-standing 2D nvdWs hexagonal FeSe with a thickness of 2.9 nm by the reaction between the oleylamine–Se complex and Fe 2+ with the assistance of Cl −, where the synergetic effects of Cl − and –NH2 lead to anisotropic growth. Inspiringly, the 2D hexagonal FeSe exhibits intrinsic antiferromagnetic order rooted in Fe 2+ and semiconducting nature. In addition, the temperature variation would result in the chemical environment changes of Fe 2+, responsible for the temperature-dependent magnetic transitions. This work promotes the potential applications of 2D hexagonal FeSe and the preparation of other 2D nvdWs materials.